Data Resource Profile: The Enhanced Prescribing Database (EPD) in Northern Ireland - Ross, Emma; Cooper, Janine; O'Reilly, Dermot; Maguire, Aideen (International Journal of Population Data Science, 2026)
Introduction The Enhanced Prescribing Database (EPD) is a comprehensive electronic database capturing detailed information on all Health and Social Care Northern Ireland (HSCNI) prescriptions dispensed in community pharmacies across Northern Ireland (the publicly funded healthcare system in Northern Ireland, equivalent to the NHS elsewhere in the United Kingdom). Established in 2010 by the Health and Social Care Business Services Organisation (HSC BSO), the EPD provides a valuable resource for monitoring prescribing practices and supporting population-based research. Methods When pharmacies in Northern Ireland submit dispensed prescriptions to the HSC BSO for reimbursement, these forms are scanned, and information is extracted from 2D barcodes. This data is initially stored in the Electronic Prescription and Eligibility System (EPES) for payment processing. The EPD is then created as a separate research database, derived from the EPES but tailored for research purposes. The inclusion of the unique Health and Care Number (HCN) facilitates linkage to other health and social care datasets within approved projects. Direct identifiers (including the HCN) are retained only within the secure environment for linkage, and are replaced with project-specific anonymous identifiers prior to researcher access. Results The EPD is held within the Health and Social Care Honest Broker Service (HSC HBS), the Secure Data Environment for Health and Social Care research in Northern Ireland. The database captures prescribing data from January 2010 onwards and is updated monthly, with data available up to December 2025 at the time of manuscript preparation. The EPD contains information on over 44 million prescribed items annually, with detailed information on dispensed items, prescriber information, patient demographics and classification data. Data quality is high, with product codes populated for over 99% of records, HCNs populated for approximately 70-90% of records, and scan rates (the proportion of prescriptions for which patient identifiers are successfully captured) improving from 74.9% in 2018/19 to 91.1% in 2024/25. Conclusion Researchers can access de-identified data via the HSC HBS following approval from the Health and Social Care Data Access Committee (HSCDAC). The EPD supports a wide range of research, including drug utilisation studies, prescribing practice evaluations, and analyses that use prescribing data as proxy indicators of treated disease. Ongoing system enhancements, including Optical Character Recognition, support incremental improvements in patient information capture and linkage completeness.